2015
DOI: 10.4236/psych.2015.69107
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning and Rational-Emotive Education: An Exploratory Investigation of Students’ Perspective

Abstract: There is no doubt about the relevance of social learning from the perspective of many groups of adults, such as teachers and researchers. However, do students share this evaluation, especially if students are socially disadvantaged? The current study explored whether rational-emotive education (REE) was a suitable concept for social learning with disadvantaged students and what to consider when students' perspective was involved. Mixed methods were used. Social problem solving was explored with a pre-post desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The challenges faced by adolescents with ASDs can be summed up as poor communication and social skills. [12] It is possible that adolescents with ASDs might have trouble taking turns in conversations. They might talk a lot about a favorite topic but find it problematic to talk about a variety of topics.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The challenges faced by adolescents with ASDs can be summed up as poor communication and social skills. [12] It is possible that adolescents with ASDs might have trouble taking turns in conversations. They might talk a lot about a favorite topic but find it problematic to talk about a variety of topics.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Studies have shown that the rational, explicit, and direct teaching of content is important for the development of stable knowledge and skills. [12] From this frame of reference, we chose the RELE, which is based on the applied principles of Rational Emotive Behavior Therapy (REBT).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations